Effectiveness of E-Content Module in Learning Set Language among Ninth Standard Students-Solomon Four Group Method of the Experimental Study - et. al., Prabakaran B, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Pedagogical methods are one of the Mathematics e-content modules of learning. The research question was raised what teaching method is more effective, whether the e-content module of learning or traditional teaching? Solomon four-group design of the experiment was managed. A convenient sampling technique is selected. Experiments are conducted in school students with 80 samples. Academic achievement test in the Mathematics unit ‘Set Language’ was used as a tool in the study. Bartlett’s Homogeneity of Variance Test, ANOVA, and LSD post-hoc tests are used for interpretation of data. The major finding explored was that the e-content module of learning positively influenced student achievement in mathematics when compared with the chalk and talk method of teaching. A recommendation of the result was a modern pedagogical method such as an e-content module of learning which is used by the teachers in the classroom as well as the students’ home for drills and practices.